National population‐based estimates for major birth defects, 2010–2014. Issue 18 (3rd October 2019) - Mai, Cara T.; Isenburg, Jennifer L.; Canfield, Mark A.; Meyer, Robert E.; Correa, Adolfo; Alverson, Clinton J.; Lupo, Philip J.; Riehle‐Colarusso, Tiffany; Cho, Sook Ja; Aggarwal, Deepa; Kirby, Russell S.
Abstract: Background: Using the National Birth Defects Prevention Network (NBDPN) annual data report, U.S. national prevalence estimates for major birth defects are developed based on birth cohort 2010–2014. Methods: Data from 39 U.S. population‐based birth defects surveillance programs (16 active case‐finding, 10 passive case‐finding with case confirmation, and 13 passive without case confirmation) were used to calculate pooled prevalence estimates for major defects by case‐finding approach. Fourteen active case‐finding programs including at least live birth and stillbirth pregnancy outcomes monitoring approximately one million births annually were used to develop national prevalence estimates, adjusted for maternal race/ethnicity (for all conditions examined) and maternal age (trisomies and gastroschisis). These calculations used a similar methodology to the previous estimates to examine changes over time. Results: The adjusted national birth prevalence estimates per 10, 000 live births ranged from 0.62 for interrupted aortic arch to 16.87 for clubfoot, and 19.93 for the 12 critical congenital heart defects combined. While the birth prevalence of most birth defects studied remained relatively stable over 15 years, an increasing prevalence was observed for gastroschisis and Down syndrome. Additionally, the prevalence for atrioventricular septal defect, tetralogy of Fallot, omphalocele, and trisomy 18 increased in this period compared to the previous periods. Active case‐finding programs generally had higher prevalence rates for most defects examined, most notably for anencephaly, anophthalmia/microphthalmia, trisomy 13, and trisomy 18. Conclusion: National estimates of birth defects prevalence provide data for monitoring trends and understanding the impact of these conditions. Increasing prevalence rates observed for selected conditions warrant further examination.